2020
DOI: 10.1097/prs.0000000000007496
|View full text |Cite
|
Sign up to set email alerts
|

Modified Buccal Myomucosal Flap Closure of Large Anterior Palatal Oronasal Fistulas

Abstract: Summary: Large oronasal palatal fistulas can be challenging to reconstruct. The authors present a modified buccal myomucosal flap repair technique and review intermediate-term outcomes. In this technique, large anterior palatal fistulas are closed in two layers. First, apposing nasal turnover flaps of vomer mucosa medially and nasal wall mucosa laterally are approximated. Second, a posteriorly based buccal flap incorporating full-thickness buccinator muscle and overlying mucosa is transposed with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The publications covered STSTs from 1989 to 2021, with one study from the 1980s, 18 five from the 1990s, 19–23 15 from the 2000s, 24,25,34–38,26–33 and 26 from 2010 to 2021 39,40,49–58,41,59–61,42–48 . The average study period was 4.14 years with a range of one week to 25 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The publications covered STSTs from 1989 to 2021, with one study from the 1980s, 18 five from the 1990s, 19–23 15 from the 2000s, 24,25,34–38,26–33 and 26 from 2010 to 2021 39,40,49–58,41,59–61,42–48 . The average study period was 4.14 years with a range of one week to 25 years.…”
Section: Resultsmentioning
confidence: 99%
“…The publications covered STSTs from 1989 to 2021, with one study from the 1980s, 18 five from the 1990s, [19][20][21][22][23] 15 from the 2000s, 24,25,[34][35][36][37][38][26][27][28][29][30][31][32][33] and 26 from 2010 to 2021. 39,40,[49][50][51][52][53][54][55][56][57][58]41,[59][60][61][42][43][44][45][46][47][48] The average study period was 4.14 years with a range of one week to 25 years.…”
Section: Categorization and Timingmentioning
confidence: 99%
“…Since then, surgeons’ interest in this flap has been increased. Many studies have demonstrated that buccal myomucosal flap is a versatile flap that can be utilized to repair a variety of small and moderate-sized head and neck defects, such as cleft palate, oroantral fistula, oropharyngeal stenosis, nasal lining and columellar defects, and glossectomy defects after tumor resection 23–27…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that buccal myomucosal flap is a versatile flap that can be utilized to repair a variety of small and moderate-sized head and neck defects, such as cleft palate, oroantral fistula, oropharyngeal stenosis, nasal lining and columellar defects, and glossectomy defects after tumor resection. [23][24][25][26][27] As proposed here, the buccal myomucosal flap for red lip reconstruction has several advantages. Anatomically, it has a welldescribed and constant blood supply sourced by the buccal or facial artery, which makes it a dependable flap that leads to soft tissue survival.…”
Section: Discussionmentioning
confidence: 99%
“…One of its distinguishing features is the potential for mucosa-to-mucosa replacement, facilitating optimal functional and aesthetic outcomes [27]. Moreover, BMF is associated with relatively low morbidity and yields optimal functional and cosmetic results [27,28 ▪ ]. However, it's important to note that the surgical elevation of BMF can present challenges as the plexus of the terminal branches in the buccal mucosa can have significant variation.…”
Section: Treatment Options For Massive Palatal Defects Following Pala...mentioning
confidence: 99%